2017
DOI: 10.1017/s0022215117001098
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus tumour status is not associated with a positive depression screen for patients with oropharyngeal cancer

Abstract: This population has a high risk for depression, but no obvious risk factors, including human papillomavirus tumour status, were associated with an elevated risk. This inability to risk-stratify patients by clinico-demographic or disease characteristics emphasises the importance of regular depression screening for all patients in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…These symptoms can include intrusive negative thoughts, avoidance of negative thoughts and behaviors, and hyperarousal symptoms (Posluszny et al, 2015). A recent retrospective study showed that 31 of 69 (44.9%) HNC patients had a positive depressive screen at diagnosis, but no obvious risk factors (including HPV status) were identified (Qualliotine et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms can include intrusive negative thoughts, avoidance of negative thoughts and behaviors, and hyperarousal symptoms (Posluszny et al, 2015). A recent retrospective study showed that 31 of 69 (44.9%) HNC patients had a positive depressive screen at diagnosis, but no obvious risk factors (including HPV status) were identified (Qualliotine et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This research identified better emotional function in the patients with HPV-associated OSPCC than in the HPV-negative patients on the EORTC QLQ-C30. Qualliotine’s retrospective review of OPSCC patients (n = 69) noted that a lower proportion of HPV-associated OPSCC patients use anti-depressants [ 31 ]. Korsten prospectively compared HPV-positive and HPV-negative OPSCC patients and identified greater post-treatment emotional function in the former group using the EORTC QLQ-C30 and the EORTC Head and Neck Cancer module (EORTC QLQ-HN35) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies did not associate worsening mental health with HPV status (Qualliotine on CES-D initial screen, Rajeev-Kumar on UW-QOL, and Shinn using both the PHQ-9 and the CES-D) [ 29 , 31 , 34 ]. Shinn performed a prospective cohort study on 130 patients with OPSCC [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients encounter trismus and a hearing deficit, which may worsen [ 71 , 72 , 74 , 75 , 76 ]. In addition, depression is a side effect that should be followed up and not neglected [ 77 , 78 ]. Radio-osteonecrosis is also a late side effect and needs reconstruction surgery [ 71 , 72 , 74 , 75 , 76 ].…”
Section: Treatment Of Tonsillar and Base-of-tongue Cancermentioning
confidence: 99%